PERBANDINGAN HASIL BELAJAR FISIKA SISWA YANG MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW DENGAN DISCOVERY-INQUIRY DI SMA - Aristin Raras; Vina Serevina; Anggara Budi Susila (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2015)
This research aims to see how the comparison of of the result of student learning Physics through cooperative learning model of Jigsaw with Discovery-Inquiry. The research has been conducted in February-April 2015 in SMAN 2 Bekasi. The research method which is used is the Quasi-Experiments method The samples were taken two classes from XI SMA Mathmatics and Science. And divided into class experiment 1 and experiment 2. The instrument which is used in the form of a multiple choice test with a score of 0-1 as many as 30 questions and five answers. The results of this study with a statistical test the "t" test and Tuckey test to be able to see the comparison. Based on the calculation, t value for 2,28 is higher than t table for n = 42 and at a significance level of 5% is 1,66. And for value of Tuckey test (Q value) is 3,12 at a significance level of 5% is 2,86. It can be concluded that the results of learning physics students using cooperative learning model jigsaw is higher than using the discovery-inquiry. Keywords : Student learning Physics, Jigsaw, Discovery-Inquiry.